Proses Berpikir Reflektif Mahasiswa Dalam Pemecahan Masalah Pada Materi Himpunan Ditinjau Dari Gaya Kognitif Berdasarkan Langkah Polya - Urip Tisngati (Beta: Jurnal Tadris Matematika, 2015)
The purpose of this study is to describe the process of reflective thinking in solving the problem of mathematic education students on the material terms of the set viewed from cognitive styles. This research is classified in the qualitative descriptive study with the case study method. The subjects in this study were students of mathematic education STKIP PGRI Pacitan in the first semester of academic year 2014/2015. The determination of the subject is by using purposive sampling, which is based on field independent and field dependent of cognitive styles. The research data taken from the test results of subjects works and interviews of subjects. Test of the credibility of the data is done by time triangulation. The data analysis technique is qualitative descriptive by Miles and Huberman. The results showed that student with field independent cognitive styles more active using reflective thinking processes than student with field dependent cognitive styles.